Collaboration between Parents and Teachers in Overcoming the Difficulties of Students in Learning Online during the Covid-19 Period - Indah Puspita Sari; Asmidir Ilyas (Current Issues in Counseling, 2021)
This research is motivated by a phenomenon that occurs in the field where the lack of good cooperation between parents and the school is evident in some parents only fully giving up the responsibility of educating or studying their children to the school, parents are busy working outside the home due to economic limitations. This study aims to reveal the collaboration between parents and teachers in overcoming the difficulties of students learning online during the Covid-19 period. This type of research uses quantitative research with a descriptive approach. The research subjects were 81 parents of students of SMA Negeri 2 Tilatang Kamang. The instrument used was a questionnaire with a Likert scale model using percentile analysis techniques. The results of this study indicate that the collaboration between parents and teachers is in the good category with an average percentage of 72.84%. Details of each aspect (1) The meeting between parents and teachers during Covid was in the quite good category. (2) School communication with parents is in good category. (3) improving children's learning outcomes is in the good category. (4) Home visits are in the good category. (5) School visits are in good category. (6) Providing data to each other is in the good category. Based on the results of the study, it is recommended that counselors increase parent-teacher collaboration by compiling a counseling program related to parent-teacher collaboration in overcoming student learning difficulties online.